Implementasi Komunikasi Efektif Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru di SDN Mekarjaya 30 Depok - Iis Dewi Lestari (SAP (Susunan Artikel Pendidikan), 2019)
Every teacher must have work motivation as a motivate from intrinsic and extrinsic to increase their jobs. Teacher work motivation can get from their headmaster. Headmaster have effectiveness communication to their teacher at school. Effectivenes communication is important to create the culture of organization at school with harmonious. Contribution of headmaster is important to have good school with positive energy and comfortable. Aim the research is to describe how the headmaster in using effectiveness communication to increase teacher work motivation at SDN Mekarjaya 30 Depok. The method of this research is descriptive. Data was collected by in the interview, observation, and literatue study. Data analysis was performed by data reduction, data presentation and conclusion on verifications. The results of this research are headmaster in SDN Mekarjaya 30 Depok implemented the effectiveness communication to the teacher. It can see from the good choosen channel by headmaster to get effectiveness communication, headmaster  understand teacher’s personality and character.  Beside that headmaster using body language as a emphasis about the information to easy understand And teacher give the feed back with emphaty and have work motivation.